2014
DOI: 10.1016/j.prosdent.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of occlusal vertical dimension on lip positions at smile

Abstract: Purpose:In full mouth reconstructive dentistry, the occlusal vertical dimension(OVD) is often increased to provide adequate restorative space or for esthetic reasons. The purpose of this study was to analyze the effect of occlusal vertical dimension on dimensional measurements of the smile. Materials and Methods:30 dental students, 12 male and 18 female between the ages of 21 -30 participated in this study. Polyvinyl Siloxane bite splints of 2mm, 4mm, 6mm, 8mm thicknesses were fabricated on stone casts mounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
0
23
1
1
Order By: Relevance
“…Recently, OVD was found to affect the positions of the lips during smile . With an increase in OVD, the position of the upper lip and the intercommissural width stay the same while the lower lip moves downwards, leading to a lower SI .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, OVD was found to affect the positions of the lips during smile . With an increase in OVD, the position of the upper lip and the intercommissural width stay the same while the lower lip moves downwards, leading to a lower SI .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, occlusal vertical dimension (OVD) was found to affect lip positions at smile . Specifically, increasing the OVD shifts the lower lip downwards, increases the interlabial gap height, increases the display zone area and lowers the smile index (SI, intercommissural width/interlabial gap height) . The width of the smile and position of the upper lip were not found to be affected by changes in OVD .…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations